2023
DOI: 10.21608/svu.2023.201258.1263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Clostridium perfringens in small ruminants

Hams M.A. Mohamed,
Manar M.H. Elfeky,
M.W. Abd Al-Azeem
et al.

Abstract: A significant foodborne pathogen as Clostridium perfringens (C. perfringens) has been linked to many diseases in sheep and goat, included; Enterotoxaemia, pulpy kidney disease,struck, and even animal mortality. So, The objective of this study is to discuss the presence of C. perfringens in small ruminants with focusing on the virulence factors, antimicrobial resistance profile, and biofilmforming capacities of the organism. A total 166 samples, (95 from sheep, 71 from goats) collected from apparently healthy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…No isolates carried the cpb, etx, or iap genes [18]. They observed prevalence rate of 25.37% of C. perfringens strains that were isolated from 134 samples.…”
Section: Discussionmentioning
confidence: 96%
“…No isolates carried the cpb, etx, or iap genes [18]. They observed prevalence rate of 25.37% of C. perfringens strains that were isolated from 134 samples.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a 2018 study by Hamza et al reported the highest prevalence of C. perfringens in apparently healthy sheep (65.45%), followed by goats (58%), buffalo (55%) and cattle (47%) [94]. In addition, other studies demonstrated the presence of multidrug resistance (MDR) patterns for commonly used antimicrobials in food animal production, including β-lactams, tetracyclines and aminoglycosides [95][96][97][98].…”
Section: Clostridium Perfringensmentioning
confidence: 99%